2018
DOI: 10.1155/2018/5031205
|View full text |Cite
|
Sign up to set email alerts
|

The Preparation and Characterization of Tourmaline-Containing Functional Copolymer p (VST/MMA/BA)

Abstract: Tourmaline was modified with vinyl triethoxysilane containing double bond to prepare the polymerizable organic vinylsiliconoxyl tourmaline (VST) and then copolymerized with methyl methacrylate (MMA) and butyl acrylate (BA) to produce the tourmaline-containing functional copolymer p (VST/MMA/BA). The structures and morphologies of VST and p (VST/MMA/BA) copolymer were characterized by IR, SEM, and EDX. The experimental results indicated that tourmaline was introduced into the copolymer via surface modification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Tourmaline is a ring-shaped borosilicate complex ore mineral with crystalline compound and molecular formula of Na (Mg, Fe, Mn, Li, Al) 3 Al 6 (BO 3 ) 3 Si 6 O 18 (O, OH, F) 4 ; it contains trace elements such as V, Cr, Zr, Mn, Ti, Sr and Ga. This complex mineral compound has characteristics of far-infrared radiation emission, spontaneous polarizability, and protective effects against electromagnetic wave, and anion -releasing effect; it is widely used in healthcare facilities [28][29][30]. Numerous studies have shown that emission of infrared and negative ions from tourmaline has positive effects against several inflammatory diseases and dermatological diseases including psoriasis and AD [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Tourmaline is a ring-shaped borosilicate complex ore mineral with crystalline compound and molecular formula of Na (Mg, Fe, Mn, Li, Al) 3 Al 6 (BO 3 ) 3 Si 6 O 18 (O, OH, F) 4 ; it contains trace elements such as V, Cr, Zr, Mn, Ti, Sr and Ga. This complex mineral compound has characteristics of far-infrared radiation emission, spontaneous polarizability, and protective effects against electromagnetic wave, and anion -releasing effect; it is widely used in healthcare facilities [28][29][30]. Numerous studies have shown that emission of infrared and negative ions from tourmaline has positive effects against several inflammatory diseases and dermatological diseases including psoriasis and AD [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of tourmaline on asphalt density, dynamic stability, and flow value were analyzed, and the micro-mechanism of tourmaline modified asphalt was also studied [25][26][27][28]. Organic tourmaline exhibits excellent storage stability due to its reduced surface polarity, which pioneer a new way for the development of mineral and copolymer composites [29]. Çelikbilek et al evaluated the performances of Tourmaline modified asphalt (TMA) mixture by the means of Grey multi-criteria evaluation model.…”
mentioning
confidence: 99%